Media Tali Laso Quick Response Code Pembelajaran Tematik Pada Siswa Inklusi - Imalia Din Indriasih (Jurnal Didaktika Pendidikan Dasar, 2020)
Learning in elementary schools, especially thematic, really requires the support of interesting and easy-to-use media by teachers and students. The development of digital media to support the achievement of learning objectives in elementary schools has been widely developed by various institutions. However, those that are suitable for the child's environment and easy to operate are still very few. The author is interested in developing media that are cheap, easy, and environmentally friendly. The methods used with the ADDIE procedure are analysis, design, development, implementation, and evaluation. The results of this media development are called TaliLaso QRC. What distinguishes TaliLaso QRC from other similar media is its application in the inclusion class so that the design is specifically designed to suit the needs of inclusive students. After being applied in the learning process of TaliLaso QRC, it shows statistical data of 91.5% increase in the average grade of the class and 90 % increase in the value of inclusive students. Then the final results of the observation showed the motivation and activeness of students in learning increased 89.5% and motivation and activeness of inclusion students reached 100%. It far exceeds the specified KKM value of 80.00.